Community Service from the Perspective of Sustainable Development Goals (SDGs): Contributions to Community Welfare and Local Economic Development - Muhammad Ade Kurnia Harahap; Wahyuni Sri Astutik; Syamsu Rijal (PT. LITERASI SAINS NUSANTARA, 2026)
This study aims to analyze community service from the perspective of Sustainable Development Goals (SDGs) and its contribution to community welfare and local economic development. The study employs a literature review method with a qualitative approach and descriptive analysis. Data were obtained from various literature sources indexed in Google Scholar and other credible websites published between 2014 and 2026. In the initial stage, 50 articles were identified, and through a rigorous selection process, 34 main articles relevant to the research objectives were selected. The findings indicate that community service plays an important role in enhancing community capacity, strengthening MSMEs, improving financial literacy, and promoting participatory local economic development. The SDGs perspective positions community service as a strategic instrument in creating inclusive and sustainable development. However, the study also identifies several challenges, including low program sustainability, limited impact evaluation, and suboptimal cross-sector collaboration in the implementation of community service programs.